Liver Fibrosis Linked to Cognitive Performance in HIV and Hepatitis C. (1st July 2016) - Valcour, Victor G.; Rubin, Leah H.; Obasi, Mary U.; Maki, Pauline M.; Peters, Marion G.; Levin, Susanna; Crystal, Howard A.; Young, Mary A.; Mack, Wendy J.; Cohen, Mardge H.; Pierce, Christopher B.; Adimora, Adaora A.; et al.
Abstract : Objective: Because HIV impairs gut barriers to pathogens, HIV-infected adults may be vulnerable to minimal hepatic encephalopathy in the absence of cirrhosis. Background: Cognitive disorders persist in up to one-half of people living with HIV despite access to combination antiretroviral therapy. Minimal hepatic encephalopathy occurs in cirrhotic patients with or without HIV infection and may be associated with inflammation. Design/Methods: A cross-sectional investigation of liver fibrosis severity using the aspartate aminotransferase to platelet ratio index (APRI) and neuropsychological testing performance among women from the Women's Interagency HIV Study. A subset underwent liver transient elastography (FibroScan, n = 303). Results: We evaluated 1479 women [mean (SD) age of 46 (9.3) years]: 770 (52%) only HIV infected, 73 (5%) only hepatitis C virus (HCV) infected, 235 (16%) HIV/HCV coinfected, and 401 (27%) uninfected. Of these, 1221 (83%) exhibited APRI ⩽0.5 (no or only mild fibrosis), 206 (14%) exhibited APRI >0.5 and ⩽1.5 (moderate fibrosis), and 52 (3%) exhibited APRI >1.5 (severe fibrosis). Having moderate or severe fibrosis (APRI >0.5) was associated with worse performance in learning, executive function, memory, psychomotor speed, fluency, and fine motor skills. In these models that adjusted for fibrosis, smaller associations were found for HIV (learning and memory) and HCV (executive functioning and attention). The severity of fibrosis, measured by FibroScan, was associated with worse performance in attention, executive functioning, and fluency. Conclusions: Liver fibrosis had a contribution to cognitive performance independent of HCV and HIV; however, the pattern of neuropsychological deficit associated with fibrosis was not typical of minimal hepatic encephalopathy.